1971
DOI: 10.1128/iai.3.6.768-773.1971
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Indigenous Gastrointestinal Microbial Flora on Duodenal Alkaline Phosphatase Activity in Mice

Abstract: Alkaline phosphatase activity was assayed by two procedures in duodenal homogenates from specific pathogen-free (SPF) mice of various ages, adult germfree mice, adult ex-germ-free mice colonized with an indigenous microflora from the SPF mice, and adult ex-germ-free mice monocontaminated with a Lactobacillus sp. indigenous to the SPF mice. In the SPF neonates, the activity remained at low levels until at least 12 days of age, increased to high levels at 20 days of age, and then fell to adult levels between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
4
31
1
Order By: Relevance
“…M-cell surfaces are enhanced sites of attachment and intestinal barrier penetration by bacteria, bacterial toxins, and virus particles (Owen and Nemanic, 1978;Shaklamov et al, 1981;Wolf et al, 1981). It has been reported that introduction of bacteria to germ-free mice (Yolton et al, 1971) and rats (Kawai, 1979) reduces intestinal alkaline phosphatase concentration, although others have found no reduction in enzyme activity beyond that consistent with shortening of villi associated with reduced enterocyte life span in conventional animals colonized by bacteria (DeBoth et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…M-cell surfaces are enhanced sites of attachment and intestinal barrier penetration by bacteria, bacterial toxins, and virus particles (Owen and Nemanic, 1978;Shaklamov et al, 1981;Wolf et al, 1981). It has been reported that introduction of bacteria to germ-free mice (Yolton et al, 1971) and rats (Kawai, 1979) reduces intestinal alkaline phosphatase concentration, although others have found no reduction in enzyme activity beyond that consistent with shortening of villi associated with reduced enterocyte life span in conventional animals colonized by bacteria (DeBoth et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional chicks, as zebrafish, tend to display a higher intestinal AP activity than germ‐free chicks 61 . However, AP activity was not found to vary significantly in pigs, 17 while it decreased along with bacterial colonization in mice and rats 62–69 . Therefore, AP activity in the intestine may be modulated by the microbiota differently depending on the animal species.…”
Section: Intestinal Alkaline Phosphatase: Biological Rolesmentioning
confidence: 96%
“…Indigenous microorganisms also influence the digestive and absorptive activities of the small bowel. The activity of alkaline phosphatase is severalfold higher in the duodenal epithelium of germfree mice (29) and rats (11) than in conventional animals. Alkaline phosphatase may play several roles in the digestive process such as absorption of cholesterol and lipids (19), vitamin D and calcium (18), and amino acids and glucose (12).…”
mentioning
confidence: 89%
“…Efforts have been made to establish models for studying the mechanisms by which the microflora exerts its influence on alkaline phosphatase activity of the intestinal epithelium (11,(27)(28)(29). In one such model, in which germfree mice were monoassociated with indigenous lactobacilli, the enzymatic activities varied depending on the source of the lactobacilli and the strain of mice (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation